Evaluation of Urinary Cytokines in Idiopathic Glomerulonephritis in a Tertiary Care Teaching Hospital (Academia Journal of Medicine, 2019)
Background: Idiopathic primary glomerular diseases include a group of disorders characterized by pathologic alterations in normal glomerular  structure and function, independent of systemic disease processes. Inflammatory cytokines, including MCP-1 and IL-6, plays an important role  in glomerular inflammation. In this study we determined whether the measurement of urinary MCP-1 and IL-6 might be useful in assessing the  role of these urinary marker in idiopathic primary glomerulonephritis and its relationship with histopathological finding. We found in result the  minimum level of MCP-1 and IL-6 was 5.6pg/ml and 7.69pg/ml and the maximum level of MCP-1 and IL-6 was 23.6pg/ml and 60.04pg/ml  respectively. The mean and standard deviation were higher in nephrotic range proteinuria than nonnephrotic proteinria. Correlation of urinary  MCP-1 and IL-6 with 24 hour urinary protein
Keywords: Urinary cytokines; Glomerulonephritis; MCP-1; IL-6